Unusual presentation of secondary CNS lymphoma with punctate intralesional and intraventricular hemorrhage - Daniel De-Liang Loh; Ira Sun; Shiong Wen Low; Pin Lin Kei (Radiology Case Reports)
Primary and secondary central nervous system lymphomas are infrequently encountered entities that present nonspecifically for which imaging plays a critical role in the diagnostic process. The conventional wisdom is that the presence of intralesional hemorrhage in an immunocompetent patient strongly counts against the diagnosis of lymphoma; however more recent evidence suggests that the distinction is more nuanced. Especially for PCNSL, there is increasing recognition that some degree of hemorrhage occurs more frequently than previously thought, and there are a number of case reports describing various types of hemorrhagic lesions that were histologically confirmed to be lymphoma. Hemorrhage in SCNSL is much rarer with only 3 cases described to date. We describe an unusual case of SCNSL with a pattern and progression of hemorrhage distinct from the prior descriptions. Awareness of the range of possible appearances of atypical presentations of CNS lymphoma is important to ensure that it is not prematurely excluded from the differential diagnosis which can delay appropriate treatment. Although rare, intralesion hemorrhage in itself should not preclude the diagnosis of lymphoma particularly when the other imaging features are congruent.